ANALYSIS OF THE EFFECT OF RICE PRODUCTION, POVERTY, AND PREVALENCE OF UNDERNOURISHMENT (POU) ON FOOD SECURITY IN INDONESIA - Citra Putri Hannida; Herman Sambodo (Universitas Sebelas Maret, 2025)
This research is motivated by the mismatch between potential and real conditions in Indonesia, resulting in food security problems. As an archipelagic, maritime, tropical, and agricultural country, Indonesia has abundant natural resource potential. Indonesia is one of the largest rice-producing countries in the world. However, Indonesia's food security condition is still low. It is proven by Indonesia's food security index, which is still below the global and Asia-Pacific averages. This research aims to analyze the influence of Rice Production, Poverty, and Prevalence of undernourishment variables on food security in Indonesia. This type of research is descriptive quantitative, using secondary data in the form of panel data for 2018-2022. The analytical method used in this research is panel data regression analysis. The results of this research show that the variables of rice production, poverty, and prevalence of undernourishment (PoU) together significantly affect food security in Indonesia. Partially, the rice production variable has a positive and insignificant effect on food security in Indonesia. The poverty variable negatively and significantly affects food security in Indonesia. The prevalence of the undernourishment variable has a positive and significant effect on food security in Indonesia.